Asignación de agua en bloques de riego frente a la baja eficiencia de distribución en el Valle Chicama - Miranda Lopez, Delmy Rene (2016)
This research was conducted at the Commission Users Ascope. This report seeks to determine the allocation of Irrigation Water Blocks, in order to obtain volumes of water to improve distribution efficiency Chicama Valley Part Baja. Currently in the Chicama Valley Part Baja water resources are insufficient for this purpose the present study was carried Water Allocation in Irrigation Blocks which is considered the allocation of water from Chicama river runoff and water seepage the river, a tributary of the River Chicama, assigned to blocks uptown Commission Users Sausal. Getting the Water Availability for agricultural purposes, adding both water leaks from around the valley and water from river runoff Chicama and given the persistently water flow forecast 50% of Rio Chicama, water availability MMC is 821,503; this amount is deducted population use water for MMC 7.54, thereby obtaining water availability for agricultural purposes in MMC 813.96., which have been assigned to 43,629.45 hectares of area under irrigation under license, without considering the 03 blocks uptown Commission Users Sausal. Agricultural requirements were calculated based on the certificates of cultivation and irrigated areas under license. Done the corresponding water balance, you can see the deficit in the valley of water supply over demand. The assignable water supply does not cover the needs required by the certificates of the crops, so that has given a proportionality factor based on the allowable gross water supply and demand, which has proceeded to the proportional allocation of water blocks. In the case of blocks uptown Commission Users Sausal, we have considered the calculations performed with the water supply of the river Quirripano.